Linguistic construction of translocal identities :|multilingual Ugandans in İstanbul - Deniz, Özge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis project investigates the linguistic identity practices of multilingual Ugandans living in İstanbul as translocal migrants. Focusing on the everyday language practices of two Ugandan women in various social spaces for a year, this linguistic ethnographic study draws on data from field observations, interviews, and audio-recordings of spontaneous conversations across the Turkish, English, and African local languages. Based on chronotopic data analysis, findings reveal how these women construct their translocal identities in İstanbul by evoking multiple chronotopes in their speech. They also demonstrate how a chronotopic shift in discourse leads to a change in what is perceived as linguistic capital.
Keywords: Multilingualism.; Identity (Philosophical concept); Women -- Uganda.